PREFERENSI PEDESTRIAN DITINJAU DARI PENGGUNAAN TROTOAR DI KORIDOR JALAN PEMUDA KOTA MAGELANG - Iwan Priyoga (Neo Teknika, 2015)
Sidewalk is a public space that is enabled for the convenience of pedestrians in the activity of walking from one place to another. Required a separate room that functioned as pedestrian paths. Sidewalks along the corridor Jalan Pemuda in Magelang City has an interesting phenomenon that the sidewalk on the east side grows activities that are not integrated and coordinated. The existence in the form of street vendors, tricycles, bicycles and even motorcycles utilize the sidewalk as the circulation path to make the condition of the pavement on the east side become irregular and interfere with pedestrians as users. While the condition of the pavement on the west side of the corridor Jalan Pemuda in Magelang City has relatively little interference as well as a sidewalk on the east side. This research was conducted to reveal the extent to which preferences utilizing pavement pedestrians to walk along the sidewalk. This phenomenon is interesting to study because it is associated with the option of pedestrians using the sidewalk as the movement path of circulation. This research is based on qualitative rationalistic approach. Rationalistic qualitative research approach is consistent with the nature of the research problem is to uncover the factors that influence the choice and pedestrian in exploiting the sidewalk along the road corridor Jalan Pemuda in Magelang City.Keywords: preferences. pedestrian, sidewalk